We go way back - Ben-Barak, Idan (Roaring Brook Press, 2023)
"What is life? How did it start? Long, long ago, no one knows exactly where or when, a tiny bubble formed that was a Little Bit Different. It was the first living cell. Everyone's ancestor. And so the story of life begins."--